Peter Gunn. Season two [videorecording (DVD)] - Edwards, Blake, 1922-2010; Stevens, Craig, 1918-2000; Albright, Lola; Bernardi, Herschel (Timeless Media Group ; Marketed by Shout! Factory LLC, 2012)
Peter Gunn is the perfect detective. Handsome, smart, two-fisted and a straight shooter. He has a girlfriend that can melt butter at twenty yards, a network of informants throughout the Los Angeles underworld, and a smokey jazz club to call home.